Determinants of University Students’ Attitudes and Intentions Toward Artificial Intelligence Education - Wang, Lei; Zhang, Qi; Gong, Yue (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Few studies have investigated students’ perceptions towards using intelligence & interactive virtual massive open online course (IMOOCs) although IMOOCs is an adaptive technique to resolve the massive open online course problems. This study aims to investigate the influence of perceived usefulness, perceived ease of use, attitude, subjective norm, and perceived behavioural control on intention to use IMOOCs based on the technology acceptance model and theory of planned behaviour. A total of 216 students were recruited as respondents and further tested the hypotheses proposed based on PLS-SEM. The results show that perceived usefulness positively influences attitude, and perceived ease of use positively influences perceived ease of use and, subsequently attitude. Meanwhile, attitude, subjective norm, and perceived behavioural control positively influence intention towards using IMOOCs. Lastly, theoretical and practical implications as well as limitations are discussed accordingly.